Research on Vehicle-ground Communication Integrated Bearing Scheme of Medium and Low Speed Maglev Transit - Biyong BIE (机车电传动)
The construction scheme of vehicle-ground communication system of Changsha maglev express line and Beijing maglev line (S1 line) and its shortcomings were analyzed. On the basis of deep study on the demand of medium-low speed maglev transit vehicle-ground communication service and main wireless communication technology, a LTE-M based full integrated carrying scheme was proposed, and the adaptability of the scheme to different frequency resources, different speed and anti-interference measures were further analyzed.